Direct observation of crystal degradation behaviour in porous crystals under low-dose electron diffraction conditions. Issue 34 (5th April 2023) - Sakamoto, Hikaru; Ohtani, Masataka
Abstract : The quantification of electron beam damage in crystalline porous materials has been investigated under low-dose electron irradiation conditions. Abstract : The quantification of electron beam damage in crystalline porous materials has been investigated under low-dose electron irradiation conditions. As a result of the systematic quantitative analysis of time-course changes in electron diffraction patterns, it was found that the unoccupied volume in the MOF crystal is a crucial factor for electron beam resistance.